Peningkatan Komunikasi Empati dan Peran Keluarga dalam Mitigasi Covid 19 di Kalangan Lansia Kabupaten Kerinci - Khairul Nuzuli, Ahmad; Hariadi, Sunarru Samsi; Rimin, Rimin (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2024)
The Covid-19 pandemic has changed lives around the world since the virus emerged in China in late 2019. In Indonesia, the surge in Covid-19 cases has made the country one of the most affected in Southeast Asia. The elderly are the most vulnerable group to the disease, with the highest mortality rate. Therefore, community empowerment, especially within the family, is key to mitigating the spread of Covid-19 among the elderly. This article explores the concept of empathetic communication in the context of the family and its important role in strengthening emotional connections and providing needed support for the elderly during the pandemic. Through a community empowerment approach, programs have been designed to improve family understanding, attitudes, and engagement in mitigating Covid-19. Evaluation of the activities showed significant improvements in all aspects after participating in the empowerment sessions. By implementing empathetic communication strategies, families can be more effective in managing conflict, increasing collaboration, and strengthening solidarity in dealing with this pandemic. The role theory in empathetic communication also clarifies how each family member has a unique role in supporting the elderly and strengthening family relationships as a whole. Thus, empowering families in understanding and implementing empathetic communication can have a positive impact in strengthening emotional connections, increasing support, and increasing involvement in Covid-19 mitigation efforts among the elderly.